The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4103/0366-6999.160487
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Low-dose Sevoflurane Inhalation and Propofol Anesthesia on the Myocardium after Carotid Endarterectomy

Abstract: Background:Myocardial infarction is an important cause of mortality after carotid endarterectomy (CEA). Sevoflurane provides myocardial protection to patients undergoing coronary surgery, but whether it also reduces the incidence of myocardial injury in CEA patients is unclear. In this study, we evaluated the cardioprotective effect of low-dose sevoflurane with propofol in patients undergoing CEA.Methods:This was a single-center, prospective, randomized study conducted between November 2011 and December 2013. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
(27 reference statements)
0
4
0
1
Order By: Relevance
“…Kuzkov et al reported that sevoflurane (induction and maintenance of anaesthesia with sevoflurane) is better than propofol (Total intravenous anaesthesia with propofol) to improve early postoperative cognitive dysfunction (31) . Wang et al results offers low-dose sevoflurane with propofol in patients undergoing CEA reduces the incidence of myocardial injury in symptomatic patients after CEA (32) . Tsujikawa et al reported that low-dose dexmedetomidine improves hemodynamic stability during the emergence and the recovery phases of general anaesthesia in patients undergoing CEA, in their randomized double-blind placebocontrol trial (29) .…”
Section: Advantages Of Ga Arementioning
confidence: 98%
“…Kuzkov et al reported that sevoflurane (induction and maintenance of anaesthesia with sevoflurane) is better than propofol (Total intravenous anaesthesia with propofol) to improve early postoperative cognitive dysfunction (31) . Wang et al results offers low-dose sevoflurane with propofol in patients undergoing CEA reduces the incidence of myocardial injury in symptomatic patients after CEA (32) . Tsujikawa et al reported that low-dose dexmedetomidine improves hemodynamic stability during the emergence and the recovery phases of general anaesthesia in patients undergoing CEA, in their randomized double-blind placebocontrol trial (29) .…”
Section: Advantages Of Ga Arementioning
confidence: 98%
“…In recent years, it has been found that pentazocine is a partial excitatoryantagonist of opioid receptors mainly agonizing κ receptors, with the same excitatory effect on δ receptors and partial antagonistic effect on µ receptors at increased doses, which, in addition to exerting good analgesic effects in clinical practice and producing little respiratory depression, can also play a myocardial protective role, but these studies are still limited to cardiac surgery and animal experiments [11] However, these studies have been limited to cardiac surgery and animal studies [11], and the myocardial protective effects of pentazocine in non-cardiac surgery have been less reported, and, in addition, some myocardial ischemia or myocardial injury may not show clinical symptoms, thus leading to missed diagnosis. The troponin (cTnI) selected in this experiment can detect even the smallest damage to myocardial injury, has very high sensitivity and speci city, and is extremely speci c for the diagnosis of myocardial injury [12,13], in addition, its detection is independent of ischemic symptoms, thus increasing sensitivity and monitoring more accurately, and has an irreplaceable position in the early identi cation of myocardial occurrence of ischemic damage.…”
Section: Discussionmentioning
confidence: 99%
“…1,5 A relação entre o tipo de anestesia e MINS continua incerta. Enquanto um estudo mostrou uma associação do sevoflurano com taxas mais baixas de MINS em comparação ao propofol (11,7% vs. 29,0%, p = 0,018), 18 outros estudos não mostraram benefício do uso de anestésicos voláteis em relação à ocorrência de MINS. 19,20 É importante identificar pacientes em risco elevado de eventos cardíacos adversos graves, com base na avaliação pré-operatória e baixa capacidade funcional (< 4 METs).…”
Section: Fatores De Riscounclassified